Impact of Digital Transformation on Reducing Money Laundering - Kadhim H. Hamad (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2026)
Digital transformation has become an important strategy for improving banking efficiency, transparency, and risk management. Meanwhile, money laundering remains a major challenge that threatens financial system stability. This study examines the impact of digital transformation on reducing money laundering in government and private banks in Babylon Governorate, Iraq. A quantitative descriptive-analytical approach was applied using questionnaire data collected from 100 bank employees. Data were analyzed using SPSS through descriptive analysis, one-sample t-test, and Pearson correlation analysis. The results indicate that digital transformation implementation has reached a significant level and contributes positively to reducing money laundering activities. The findings highlight the importance of digital infrastructure, employee capabilities, and technology-based monitoring systems in strengthening anti-money laundering practices in banking institutions.